Aberrant DNA Methylation-Mediated FOXF2 Dysregulation Is a Prognostic Risk Factor for Gastric Cancer - Zhang, Cheng; Li, Yong-Zhi; Dai, Dong-Qiu (Frontiers in Molecular Biosciences, 2021)
Background: The prognosis of gastric cancer (GC) patients is poor. The effect of aberrant DNA methylation on FOXF2 expression and the prognostic role of FOXF2 methylation in GC have not yet been identified. Methods: The RNA-Seq and gene methylation HM450 profile data were used for analyzing FOXF2 expression in GC and its association with methylation level. Bisulfite sequencing PCR (BSP) was performed to measure the methylation level of the FOXF2 promoter region in GC cell lines and normal GES-1 cells. The cells were treated with the demethylation reagent 5-Aza-dC, and the mRNA and protein expression levels of FOXF2 were then measured by qRT-PCR and western blot assays. The risk score system from SurvivalMeth was calculated by integrating the methylation level of the cg locus and the corresponding Cox regression coefficient. Results: FOXF2 was significantly downregulated in GC cells and tissues. On the basis of RNA-Seq and Illumina methylation 450 data, FOXF2 expression was significantly negatively correlated with the FOXF2 methylation level (Pearson’s R = -0.42, P < 2.2e-16). The FOXF2 methylation level in the high FOXF2 expression group was lower than that in the low FOXF2 expression group. The BSP assay indicated that the methylation level of the FOXF2 promoter region in GC cell lines was higher than that in GES-1 cells. The qRT-PCR and western blot assay showed that FOXF2 mRNA and protein levels were increased in GC cells following treatment with 5-Aza-Dc. The methylation risk score model indicated that patients in the high risk group had poorer survival probability than those in the low risk group (HR = 1.84 (1.11–3.07) and P = 0.0068). FOXF2 also had a close transcriptional regulation network with four miRNAs and their corresponding target genes. Functional enrichment analysis of the target genes revealed that these genes were significantly related to several important signaling pathways. Conclusion: FOXF2 was downregulated due to aberrant DNA methylation in GC, and the degree of methylation in the promoter region of FOXF2 was related to the prognosis of patients. The FOXF2/miRNAs/target genes axis may play a vital biological regulation role in GC.